Mutation of Aspergillus sp. using Ultraviolet Light and Nitrous Acid for Amylase Production from Banana Peels - Oshoma, Cyprian Erumiseli; Akor, Johnson Oche; Ikhajiagbe, Beckley; Ikenebomeh, Marcel James (Makara Journal of Science, 2022)
Strain improvement through mutagenesis is important in the commercial development of microbial fermentation. This study aimed to produce amylase from banana (Musa sapientum) peels by using mutant Aspergillus sp. strains obtained via ultraviolet (UV) radiation and nitrous acid-based mutagenesis. Results revealed that banana peels pretreated with 0.8 N HCl had a biomass yield of 3.02 g/L and amylase activity of 2.81 U/L. Of the UV mutants, strain AUV1 had the highest biomass and amylase activity of 4.50 ± 0.21 g/L and 3.46 ± 0.14 U/L, respectively. Subsequently, HNO2 mutants showed that strain ANA6 had 30.64% and 60.85% higher amylase activity than AUV1 and the wild strain, respectively. This study showed that banana peels can be utilized for amylase production. In addition, UV and HNO2 are effective mutagens for Aspergillus sp. strain improvement to enhance amylase productivity.